2019
DOI: 10.1002/jcc.26137
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation QTAIM for scoring molecular wires in E‐fields for molecular electronic devices

Abstract: The effect of a varying, directional E x, E y, and E z electric field on the ethene molecule was investigated using next‐generation quantum theory of atoms in molecules (QTAIM). Despite using low E‐field strengths that are within the realm of experiment and do not measurably alter the molecular geometry, significant changes to the QTAIM properties were observed. Using conventional QTAIM, the shifting of the C─C and C─H bond critical points (BCPs) demonstrates polarization through an interchange in the size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
1
21
1
Order By: Relevance
“…For values of the ellipticity ε > 0, the shortest and longest axes of the elliptical distribution of ρ(r b ) are associated with the λ 1 and λ 2 eigenvalues, respectively, and the ellipticity is defined as ε = jλ 1 j/jλ 2 j À 1. We earlier demonstrated that the most preferred direction for bond displacement, corresponding to most preferred direction of electronic charge density displacement, is the e 1σ eigenvector of the stress tensor [48]. Previously, we established the stress tensor trajectory T σ (s) classifications of S and R based on the counterclockwise (CCW) versus clockwise (CW) torsions for the e 1σ .dr components of T σ (s) for lactic acid and alanine [30].…”
Section: S C H E M Ementioning
confidence: 99%
See 1 more Smart Citation
“…For values of the ellipticity ε > 0, the shortest and longest axes of the elliptical distribution of ρ(r b ) are associated with the λ 1 and λ 2 eigenvalues, respectively, and the ellipticity is defined as ε = jλ 1 j/jλ 2 j À 1. We earlier demonstrated that the most preferred direction for bond displacement, corresponding to most preferred direction of electronic charge density displacement, is the e 1σ eigenvector of the stress tensor [48]. Previously, we established the stress tensor trajectory T σ (s) classifications of S and R based on the counterclockwise (CCW) versus clockwise (CW) torsions for the e 1σ .dr components of T σ (s) for lactic acid and alanine [30].…”
Section: S C H E M Ementioning
confidence: 99%
“…In extraterrestrial regions, several molecular and ionic species in excited states generated by a strong electric field which can polarize chirality have been observed [47]. Recently, some of the current authors applied a directional (±) E ‐field on the ethene molecule and demonstrated atomic polarization of the shifted C–C and C–H BCPs [48]. The recent Perspective by Shaik et al considers the prospects of oriented external‐electric‐fields, and other electric‐field types, as “smart reagents,” for the control of reactivity and structure for chemical catalysis [49].…”
Section: Introductionmentioning
confidence: 99%
“…The p and q are the 3-D paths that are constructed from the values of the least (e 1 ) and most (e 2 ) preferred directions of electronic charge density accumulation along the bond-path, referred to as r . For further discussions on the construction of bond-path framework set B{p ,q ,r } [31][32][33][34][35][36][37][38][39][40][41] , see the Supplementary Materials S2 .…”
Section: Theory and Methodsmentioning
confidence: 99%
“…For values of the ellipticity ε > 0, the shortest and longest axes of the elliptical distribution of ρ (r b ) are associated with the λ 1 and λ 2 eigenvalues, respectively, and the ellipticity is defined as ε = |λ 1 |/|λ 2 |-1. We earlier demonstrated that the most preferred direction for bond displacement, corresponding to most preferred direction of electronic charge density displacement, is theε 1σ eigenvector of the stress tensor [48]. Previously, we established the stress tensor trajectory T σ (s ) classifications of S and R based on the counterclockwise (CCW) vs. clockwise (CW) torsions for thee 1σ .dr components of T σ (s ) for lactic acid and alanine [30].…”
Section: Theoretical Background and Computational Detailsmentioning
confidence: 99%
“…In extraterrestrial regions, several molecular and ionic species in excited states generated by a strong electric field which can polarize chirality have been observed [47]. Recently, some of the current authors applied a directional (±)E -field on the ethene molecule and demonstrated atomic polarization of the shifted C-C and C-H bond critical points (BCPs ) [48] . The recent Perspective by Shaiket al .…”
Section: Introductionmentioning
confidence: 99%